Sosialisasi Proses dan Tahapan Pengadaan Tanah sesuai Regulasi untuk Lokasi Komplek Perkantoran Pemerintah Provinsi Papua Tengah di Desa Kadaridi, Distrik Wanggar Makmur, Kabupaten Nabire, Provinsi Papua Tengah - Robby Oksa Cornely; Komarudin Komarudin; Ruslin Chaerul Cora; Ronny Sung; Parapat Gultom; Suherwin Suherwin (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
The purpose of this community service is to increase understanding and knowledge related to the processes and stages according to the regulations governing land acquisition and the process of calculating the value of compensation in accordance with Law No. 2 of 2012 Article 1 Number 10. The specific target in this community service is the community in Karadiri Village, Wanggar Makmur District, Nabire Regency, Central Papua Province to know and understand the processes and stages according to the regulations governing land acquisition and the process of calculating compensation values according to Law No. 2 of 2012 Article 1 Number 10 so as not to raise concerns about the rights taken due to land acquisition carried out in Karadiri Village, Wanggar Makmur District, Nabire Regency, Central Papua Province. From this community service, the results show that there is an increase in the understanding of the village community towards land acquisition for the public interest so that the village community voluntarily releases their land rights by getting compensation payments which aim to provide land for the implementation of development in order to improve the welfare and prosperity of the nation, state and community while still guaranteeing the legal interests of the Eligible Parties in accordance with Constitution No. 12/2012 article 3.